2022
DOI: 10.3389/fphys.2022.854385
|View full text |Cite
|
Sign up to set email alerts
|

Motor Unit Number Estimation of the Second Lumbrical Muscle in Human Hand

Abstract: The number of motor units of the lumbrical muscles in human hand has not been explored. The objective of this study was to fill this gap by estimating the number of motor units in the second lumbrical muscle. Compound muscle action potential scan of the second lumbrical muscle was performed in 12 healthy subjects, with 10 of them being tested on two separate occasions. Motor unit number estimation (MUNE) was derived from the MScanFit program. The average MUNE of the second lumbrical muscle was 41.6 ± 2.1 (mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
3
0
1
Order By: Relevance
“…The results on MScanFit MUNE of the SL muscle were similar to a previous study in a United States (US) center also performed by our group, although the CMAP amplitude was slightly smaller in the current study (Zong et al, 2022a ). To the best of our knowledge, these are only two studies on MUNE of the SL muscle.…”
Section: Discussionsupporting
confidence: 92%
“…The results on MScanFit MUNE of the SL muscle were similar to a previous study in a United States (US) center also performed by our group, although the CMAP amplitude was slightly smaller in the current study (Zong et al, 2022a ). To the best of our knowledge, these are only two studies on MUNE of the SL muscle.…”
Section: Discussionsupporting
confidence: 92%
“…El análisis por el software MScanFit toma en promedio 3 minutos (Bostock, 2016). El procedimiento total puede completarse entre 10 a 20 minutos aproximadamente (Zong, Lu, Chen, Deng, et al, 2022), .…”
Section: Nombre De La Fuente: Propiounclassified
“…Existing studies reported that the test–retest repeatability of MScanFit MUNE was excellent using the same electrode for CMAP scan recordings. For example, the ICC of test–retest repeatability achieved 0.93, 0.90, and 0.96 in our previous studies on the abductor hallucis ( Li et al, 2018 ), the anconeus ( Zong et al, 2022b ), and the second lumbrical ( Zong et al, 2022a ) muscles, respectively. ICCs greater than 0.8 were also reported for MScanFit MUNE in three repeated tests on the APB, FDI, and ADM muscles ( Higashihara et al, 2020 ).…”
Section: Discussionmentioning
confidence: 74%